(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2010)
Companies have lots of precious data lying around throughout their networks that needs to be moved from one place to another such as from one business centre to another or to a data warehouse for analysis. The problem is that the data lies in different sorts of heterogeneous systems, and therefore in all sorts of formats. To accumulate data at one place and to make strategic decisions we need a data warehouse system. This consists of extract, transform and load (ETL) software, which extract data from various resources, transform it into new data formats according to required information needs, and then load it into desired data structure(s). Such softwares take enormous time for the purpose. To deal with the problem of time taken by ETL process, in this paper we are presenting a new technique of ETL using pipelining. We had divided ETL process into various segments which worked simultaneously using pipelining.